Primary spontaneous inguinal endometriosis: Two cases with emphasis on the diagnostic approach - Ching-Wen Chou; Po-Ta Lai; Chu-Chun Huang; Jin-Bon Hong; Yi-Jou Tai (Elsevier, 2023)
Objective: While endometriosis is common, inguinal endometriosis with hernia is rarely observed, making its preoperative diagnosis challenging. Case report: We report two cases of inguinal endometriosis with different presentations and focus on tailored surgical treatment. The two patients in our series presented with painful swelling in the right groin area. Surgery and pathological examination confirmed the diagnosis of endometriosis in both cases. Herniorrhaphy and excision of the extraperitoneal round ligament were performed in one patient with concomitant inguinal endometriosis and indirect inguinal hernia. Conclusion: We highlight the importance of the preoperative evaluation of concomitant pelvic endometriosis, round ligament involvement, and endometriosis within the inguinal hernia sac. Inguinal endometriosis with or without hernia should be considered even in reproductive-aged women without a previous medical and surgical history. Postoperative hormonal therapy, including dienogest, can be considered to prevent disease recurrence.